A Prospective Phase II Study of Pegaspargase-COEP Plus Radiotherapy in Patients With Newly Diagnosed Extra-Nodal NK/T-Cell Lymphoma - Hu, Shaoxuan; Lin, Ningjing; Liu, Jiaxin; Sun, Yan; Liu, Weiping; Wang, Xiaopei; Xie, Yan; Song, Yuqin; Wen, Yi; Zhu, Jun (Frontiers in Oncology, 2022)
Background The optimal first-line treatment for extra-nodal NK/T-cell lymphoma (ENKTL) has not been well-defined. This study aimed to evaluate the efficacy and safety of pegaspargase, cyclophosphamide, vincristine, etoposide and prednisone (COEPL) regimen combined with radiotherapy for patients with newly diagnosed ENKTL. Methods Our study is a prospective, open-label clinical trial. Patients with newly diagnosed ENKTL and an ECOG performance status of 0 to 2 were eligible for enrollment. For patients with stage I/II nasal ENKTL, treatment included 2 cycles of induction COEPL regimen followed by concurrent chemoradiotherapy, then by 2 cycles of COEPL regimen as consolidation. For patients with stage III/IV or primary extra-nasal ENKTL, treatment included 6-8 cycles of COEPL regimen with or without radiotherapy to local sites, and autologous stem cell transplantation was given in selected patients. Results A total of 80 patients were enrolled. The median age was 41 years (range, 15-76 years). Sixteen patients (20%) had stage III/IV disease, and 10 (12.5%) had a PINK score≥2. Complete response and overall response rates were 75.9% and 87.3%, respectively. With a median follow-up of 41.4 months (range 2.7-76.2 months), the 3-year progression-free survival (PFS) and overall survival (OS) rates were 71.3% (95%CI 61.1-81.5%) and 73.3% (95%CI 63.1-83.5%), respectively. For patients with stage I/II nasal ENKTL (n=62), the 3-year PFS and OS were 78.1% and 81.2%, respectively. For patients with stage III/IV or primary extra-nasal ENKTL (n=18), 3-year PFS and OS were 48.1% and 45.7%, respectively. Major grade 3-4 adverse events were anemia (21.3%), leucopenia (22.5%), neutropenia (18.8%), and thrombocytopenia (7.6%). No treatment-related death was observed. Conclusions Pegaspargase-COEP chemotherapy in combination with radiotherapy is highly effective and safe for patients with newly diagnosed ENKTL.